2017
DOI: 10.18632/oncotarget.16405
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic study of invasive micropapillary carcinoma of the breast

Abstract: Invasive micropapillary carcinoma (IMPC) is a rare subtype of breast carcinoma. It is presumed to be more aggressive than invasive ductal carcinoma (IDC), though it is uncertain whether the prognoses of IMPC and IDC differ. In this retrospective study, we compared the clinicopathologic characteristics and survival between 170 female patients with IMPC (pure or mixed with IDC) and 728 with pure IDC. The IMPC patients had higher clinical stages and histologic grades, higher incidences of lymphovascular invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 28 publications
1
50
0
5
Order By: Relevance
“…Twenty-five studies were excluded for not providing adequate, detailed statistics or not comparing with IDC. Thus, based on the criteria described above, 14 publications were eligible for inclusion in this meta-analysis [ 12 , 17 , 19 30 ]. The search strategy and filters applied are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five studies were excluded for not providing adequate, detailed statistics or not comparing with IDC. Thus, based on the criteria described above, 14 publications were eligible for inclusion in this meta-analysis [ 12 , 17 , 19 30 ]. The search strategy and filters applied are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reports have been published in the past three decades to compare the prognostic difference between IMPC and IDC [ 12 , 17 , 19 30 ]. Chen et al [ 20 ], using the US National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) database, found that the overall prognostic results of IMPC were similar to those of IDC and showed a more favorable DSS than IDC patients, although lymph node metastasis was more common in the former.…”
Section: Discussionmentioning
confidence: 99%
“…While histological type, lymphovascular invasion (LVI), number of involved sentinel lymph nodes and extranodal extension were assumed to attribute to lymph node involvement of IDC, and their effects on IMPC need to be further research [ 29 32 ]. Thus, currently almost all IMPC patients were treated according to standard IDC treatments [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outcome data are controversial. However, increased lymphovascular invasion is seen in this special subtype compared to IBC NST [4,5,[83][84][85][86][87][88][89][90].…”
Section: Invasive Micropapillary Breast Carcinomamentioning
confidence: 99%